SISTEM PELAPORAN KEBAKARAN PINTAR DENGAN DETEKSI LOKASI DAN VALIDASI BUKTI VISUAL OTOMATIS - Sanjaya, Anas; Widiono, Suyud (LPPM UNIVERSITAS BINA INSAN, 2025)
Fire is a disaster that requires a fast, accurate, and integrated reporting system to be managed effectively. However, the manual reporting process often causes delays in information delivery, limited verification, and a lack of visual evidence. This research aims to develop a web- and mobile-based fire reporting application using the Waterfall development method. The application integrates GPS to automatically detect incident locations and includes a visual evidence upload feature to improve reporting accuracy. Black-box testing results show that all features work properly and meet user requirements. The system accelerates the reporting process from approximately 15 minutes to 2 minutes, facilitates report verification, and provides real-time notifications to officers. The findings indicate that this fire reporting application is a practical digital solution to improve fire management efficiency and has strong potential for broader implementatio